A bridge or a ledge? The bidirectional relationship between vocational education and training and disability. (3rd July 2019) - Pullman, Ashley
ABSTRACT: Although prior research reveals varying levels of inequality in post-secondary attainment for individuals with disabilities, vocational education and training (VET) appears to be more accessible for this group in Canada. Measures of accessibility become more complex, however, when they consider a bidirectional relationship that emphasizes education as a critical juncture that is associated with the later likelihood of developing a disability. The following study deepens insight into VET attainment among people with disabilities by exploring how credential rates differ by disability severity, type, source, and timing. A series of multinomial logistic regression models that examine different operationalisations of disability status demonstrate that greater VET attainment rates for individuals with disabilities are, in part, due to the increased risk of a work-related injury or illness and/or the development of a disability after the completion of education. Nevertheless, compared to attainment at the university degree level, VET is more accessible across different types of disabilities and at higher severity levels. The implications arising from this study suggest that coarsened measures of disability status often obscure the bidirectional nature of educational inequality, from the increased risk of developing a disability at certain levels of education to greater barriers for specific conditions.